Let's define \( x \) as the height of Cassandra’s younger brother in inches. According to the problem, Cassandra's height (63 inches) is described as 6 inches less than 3 times her younger brother's height. This leads to the following equation:
\[
63 = 3x - 6
\]
To write it in the form \( px + q = r \), we need to rearrange the equation.
Adding 6 to both sides gives:
\[
63 + 6 = 3x
\]
\[
69 = 3x
\]
Now we put this in the form \( px + q = r \):
\[
3x + 0 = 69
\]
From your prompt, it looks like you want to express it more clearly with placeholders. So we can format it as:
\[
3x + 0 = 69
\]
where:
- \( p = 3 \)
- \( q = 0 \)
- \( r = 69 \)
If we put this in the format you specified, it can be written as:
3x + 0 = 69
If you had a different structure in mind, please clarify! But based on what you've written, this should work.
Now, to solve for \( x \), we have:
\[
x = \frac{69}{3} = 23
\]
So, Cassandra’s younger brother is 23 inches tall.